KEBAKARAN HUTAN KALIMANTAN SEBAGAI INSPIRASI PADA RANCANGAN PAKAIAN READY TO WEAR - Prameswari, Mentari Widyani; Siagian, Marissa Cory A. (ATRAT: Jurnal Seni Rupa, 2019)
Borneo rain forests have been known as the lungs of the world but now their sustainability is threatened by forest-fires which affect millions of people who experience respiratory problems due to burning smoke and dead animal or habitat loss. This research raises the phenomenon of Borneo rainforest-fires as inspiration in the design of ready-to-wear clothing by composing realist motif to represent the impact of forest-fires using engineering printing and beads embellishment to reinforce details. This resreach uses qualitative methods, including study of literature to obtain data and exploration of digital imaging as development of visual composition of Borneo rainforest-fires, interviews and observations to understand more about the character of Borneo rainforests and its processing in fashion products. This research resulted designs of ready-to-wear clothing inspired by Borneo rainforest-fires through motifs and beads as an embellishment to reinforce details without covering the character’s motives. Therefore it can open the potential for natural phenomena as an inspiration in the development of fashion productsKeywords: Tropical Forest, Fire Forest, Embellishment, Digital Printing, Ready to Wear___________________________________________________________________ Hutan Kalimantan telah diakui sebagai paru-paru dunia namun kini kelestariannya terancam oleh pembakaran hutan yang berdampak pada jutaan orang yang mengalami gangguan pernafasan karena asap pembakaran dan hewan mati terpanggang atau kehilangan habitat. Penelitian ini mengangkat fenomena kebakaran hutan Kalimantan sebagai inspirasi dalam rancangan pakaian ready to wear dengan membuat komposisi motif realis untuk merepresentasikan dampak kebakaran hutan menggunakan teknik engineering printing dan memanfaatkan beads embellishment untuk mempertegas detail motif. Penelitian ini menggunakan metode kualitatif yaitu studi literatur untuk mendapatkan data kehutanan, teori desain serta eksplorasi digital imaging sebagai pengembangan komposisi visual kebakaran hutan Kalimantan, wawancara serta observasi untuk memahami lebih dalam karakter hutan Kalimantan dan pengolahannya dalam produk fesyen. Penelitian ini menghasilkan perancangan busana ready to wear yang terinspirasi dari kebakaran hutan Kalimantan melalui motif dan beads sebagai embellishment untuk mempertegas detail tanpa menutupi karakter motif, sehingga dapat menjadi potensi fenomena alam sebagai inspirasi dalam pengembangan produk fesyen.Kata Kunci: Hutan Tropis, Kebakaran Hutan, Embellishment, Digital Printing, Ready to Wear